A Retrospective Cohort Study of Longitudinal Audiologic Assessment in Single and Fractionated Stereotactic Radiosurgery for Vestibular Schwannoma. Issue 6 (19th June 2019) - Khattab, Mohamed H; Sherry, Alexander D; Whitaker, Ryan; Wharton, David M; Weaver, Kyle D; Chambless, Lola B; Cmelak, Anthony J; Attia, Albert
Abstract: BACKGROUND: Fractionated stereotactic radiosurgery (SRS) for vestibular schwannomas (VS) has been theorized to allow for tumor control with higher rates of hearing preservation in selected patients with useful hearing. However, there is a paucity of literature with formal audiologic measures of hearing preservation to support the standard use of fractionated SRS in VS. We hypothesized that fractionation would diminish the amount of hearing damage. OBJECTIVE: To evaluate the relationship between audiologic performance and SRS fractionation scheme. METHODS: We performed an IRB-approved retrospective review of patients treated with 1, 3, or 5 fraction SRS for VS at our institution from 1998 to 2016. Pre- and post-SRS audiograms with speech awareness threshold (SAT) in treated and contralateral ears were obtained. Contralateral ear measurements were used for hearing normalization to account for presbycusis. RESULTS: Fifty-six patients with median audiologic follow-up 2.0 yr (mean 2.66 yr, min-max 0.50-9.45 yr) were included. Patients treated with single fractionation had a significantly worsened SAT (dB) compared to patients treated with 5 fractions ( P  = .008) and compared to all multifraction patients ( P  = .009) at 12 to 24 mo follow-up. CONCLUSION: This retrospective analysis supports the use of fractionated SRS to preserve hearing in patients with VS. SAT can be used as an objective metric of hearing response to radiosurgery. Graphical Abstract: